SBEToolbox: A Matlab Toolbox for Biological Network Analysis. (January 2013) - Konganti, Kranti; wang, Gang; Yang, Ence; Cai, James J.
We present SBEToolbox (Systems Biology and Evolution Toolbox), an open-source Matlab toolbox for biological network analysis. It takes a network file as input, calculates a variety of centralities and topological metrics, clusters nodes into modules, and displays the network using different graph layout algorithms. Straightforward implementation and the inclusion of high-level functions allow the functionality to be easily extended or tailored through developing custom plugins. SBEGUI, a menu-driven graphical user interface (GUI) of SBEToolbox, enables easy access to various network and graph algorithms for programmers and non-programmers alike. All source code and sample data are freely available athttps://github.com/biocoder/SBEToolbox/releases .